Emotional Intelligence in Islamic Education - Abidin, Zainul; Dafrizal, Dafrizal; Ramadhani, Ramadhani (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2025)
One important component for being able to live in society is the ability to manage emotions well. Research conducted by Goleman shows that intelligence quotient contributes only about twenty percent to a person's success, with the remaining eighty percent determined by a group of factors called emotional intelligence. The reality today is that a high intelligence quotient does not necessarily lead to success or a happy life. People who are highly intelligent but have unstable emotions and are easily offended often make mistakes in determining and solving life problems because they cannot concentrate. Their emotions are undeveloped, unburdened, and they often change when facing problems and behave towards others in a way that causes a lot of conflict. Poorly managed emotions also make it easy for others to enthusiastically agree to something, but then quickly change their minds and refuse, thereby disrupting the cooperation that has been agreed upon with others. Thus, the man fails. Islamic education pays close attention to this issue. This can be seen in the task of Islamic education, which is to guide and direct the growth and development of human beings from stage to stage of the students' lives in order to achieve optimal performance.